Pengaruh Strategi Active Learning Terhadap Peningkatan Hasil BelajarSiswa Sekolah Dasar - Didit Darmawan; Mujia Arrizhma (CV. Kurnia Grup, 2026)
The national curriculum, which emphasizes the mastery of 21st-century skills, requires the implementation of student-centered learning. However, traditional teaching approaches are still widely used in elementary schools, resulting in low student engagement in the learning process and suboptimal learning outcomes. Therefore, a study is needed to analyze the effectiveness of active learning strategies in improving the learning outcomes of elementary school students. This study aims to examine the influence of active learning strategies on elementary school students’ learning outcomes in the cognitive, affective, and psychomotor domains. The method employed is a Systematic Literature Review (SLR), analyzing ten scientific articles from indexed national journals and relevant academic sources. Data analysis was conducted using qualitative descriptive methods through the stages of literature selection, categorization of findings, data synthesis, and interpretation of relationships between variables. The results of the study revealed that active learning strategies consistently improved student learning outcomes across various subjects. The implementation of these strategies was shown to enhance student engagement, learning motivation, conceptual understanding, critical thinking skills, and collaboration skills through various learning models, such as card sorting, mind mapping, team quizzes, and poster comments. Based on the research results, active learning strategies can serve as an effective alternative for improving the quality of the learning process and outcomes for elementary school students, as well as supporting the implementation of student-centered learning.